BMP-2 delivery strategy modulates local bone regeneration and systemic immune responses to complex extremity trauma. (7th January 2021) - Vantucci, Casey E.; Krishan, Laxminarayanan; Cheng, Albert; Prather, Ayanna; Roy, Krishnendu; Guldberg, Robert E.
Abstract : Bone nonunions remain compelling orthopedic challenges. Bone morphogenetic protein-2 (BMP-2) delivered in a heparin microparticle (HMP) delivery system improved local bone regeneration compared to BMP-2 delivered in the clinical standard collagen sponge. Abstract : Bone nonunions arising from large bone defects and composite injuries remain compelling challenges for orthopedic surgeons. Biological changes associated with nonunions, such as systemic immune dysregulation, can contribute to an adverse healing environment. Bone morphogenetic protein 2 (BMP-2), an osteoinductive and potentially immunomodulatory growth factor, is a promising strategy; however, burst release from the clinical standard collagen sponge delivery vehicle can result in adverse side effects such as heterotopic ossification (HO) and irregular bone structure, especially when using supraphysiological BMP-2 doses for complex injuries at high risk for nonunion. To address this challenge, biomaterials that strongly bind BMP-2, such as heparin methacrylamide microparticles (HMPs), may be used to limit exposure and spatially constrain proteins within the injury site. Here, we investigate moderately high dose BMP-2 delivered in HMPs within an injectable hydrogel system in two challenging nonunion models exhibiting characteristics of systemic immune dysregulation. The HMP delivery system increased total bone volume and decreased peak HO compared to collagen sponge delivery of the same BMP-2 dose. Multivariate analyses of systemic immune markers showed the collagen sponge group correlated with markers that are hallmarks of systemic immune dysregulation, including immunosuppressive myeloid-derived suppressor cells, whereas the HMP groups were associated with immune effector cells, including T cells, and cytokines linked to robust bone regeneration. Overall, our results demonstrate that HMP delivery of moderately high doses of BMP-2 promotes repair of complex bone nonunion injuries and that local delivery strategies for potent growth factors like BMP-2 may positively affect the systemic immune response to traumatic injury.